Comparison of anti-inflammatory effects of intense pulsed light with tobramycin/dexamethasone plus warm compress on dry eye associated meibomian gland dysfunction - Yu-Fei Gao; Rong-Jun Liu; Ya-Xin Li; Chenmilu Huang; Yi-Yun Liu; Chen-Xi Hu; Hong Qi (International Journal of Ophthalmology, 2019)
AIM: To compare the anti-inflammatory effects of intense pulsed light (IPL) with tobramycin/dexamethasone plus warm compress through clinical signs and cytokines in tears. METHODS: Eighty-two patients with dry eye disease (DED) associated meibomian gland dysfunction (MGD) were divided into two groups. Group A was treated with IPL, and Group B was treated with tobramycin/dexamethasone plus warm compress. Ocular Surface Disease Index (OSDI), tear film breakup time (TBUT), corneal fluorescein staining (CFS), meibomian gland expressibility (MGE), meibum quality, gland dropout and tear cytokine levels were evaluated before treatment, 1wk and 1mo after treatment. RESULTS: TBUT in Group A was higher (P=0.035), and MGE score was lower than Group B at 1mo (P=0.001). The changes of interleukin (IL)-17A and IL-1β levels in tears were lower in Group A compared with that in Group B at 1wk after treatment (P=0.05, P=0.005). CONCLUSION: Treatment with IPL can improve TBUT and MGE and downregulate levels of IL-17A and IL-1β in tears of patients with DED associated MGD better than treatment with tobramycin/dexamethasone plus warm compress in one-month treatment period.